â€œPengaruh Motivasi Terhadap Kinerja Karyawan Pada Rumah Makan Asela Sampangâ€ - Alfi Hasaniyah (Yos Soedarso Economic Journal (YEJ), 2019)
RM Asela Sampang is a restaurant that is engaged in the processing of marine fish located in the district of Sampang. One of the efforts to improve employee performance in a business environment on an ongoing basis, employees can psychologically develop all the potentials and abilities that exist in him to do his work so that maximum results are obtained.This study was conducted to determine the effect and motivational factors on employee performance at RM Asela Sampang. The study uses multiple linear regression analysis with the results of the motivation calculation test (X) effect on the dependent variable that is performance (Y) with an R value of 0.727 or 72.2%. While the calculation results of the independent variables namely motivation (X) have an effect on the fabric (Y) can be proven true. R squared or determinant R values of 0.574 or 57.4% influence simultaneously while the rest (100% - 57.4% = 42.6%) are influenced by other factors not examined in this study.Â Keywords: Motivation; Employee Performance